ROLE OF STANDARD TRADERS IN OVERCOMING UNEMPLOYMENT RATE IN GOWA DISTRICT (CASE STUDY OF SOMBA OPU DISTRICT) - Achsanuddin UA, Anur; Fitrianti, A. Nur; Sansan, Nursamsi (Perpustakaan dan Penerbitan Unismuh Makassar, 2019)
This study is to find out how the role of street vendors in overcoming the unemployment rate in Gowa Regency (case study of Somba Opu District). The type of research used in this research is descriptive qualitative research. The results obtained by the researchers are that street vendors in Somba Opu District have a very important role in tackling the unemployment rate, where there are many business opportunities for those who are not accommodated in the formal sector and for those who still have low education where they can actualize by becoming a trader.